Approximate solutions for the inextensible Heisenberg antiferromagnetic flow and solitonic magnetic flux surfaces in the normal direction in Minkowski space - Körpınar, Talat; Demirkol, Rıdvan Cem; Körpınar, Zeliha (Elsevier GmbH, 2021)
Motivated by recent researches in magnetic curves and their flows in different types of geometric manifolds and physical spacetime structures, we compute fractional Lorentz force equations associated with the magnetic n-lines in the normal direction in Minkowski space. Fractional evolution equations of magnetic n-lines due to inextensible Heisenberg antiferromagnetic flow are computed to construct the soliton surface associated with the inextensible Heisenberg antiferromagnetic flow. Then, their approximate solutions are investigated in terms of magnetic and geometric quantities via the conformable fractional derivative method. By considering arc-length and time-dependent orthogonal curvilinear coordinates, we finally determine the necessary and sufficient conditions that have to be satisfied by these quantities to define the Lorentz magnetic flux surfaces based on the inextensible Heisenberg antiferromagnetic flow model in Minkowski space. © 2021 Elsevier GmbH
2-s2.0-85102794313
Keywords: Geometric phase; Heisenberg antiferromagnetic flow; Lorentz force; Magnetic field lines; Magnetic flux surface